Reindustrialization Plan Using the DPSIR and TOPSIS Methods - Cardoso, Wagner; Siqueira, Regiane Máximo; Ferraz, Diogo (Emerging Science Journal, 2025)
(De)industrialization is a phenomenon that affects the economic development of developed and developing countries. However, there is a lack of studies that evaluate strategies to promote the industrialization of a country through the information of industry experts. Objective: this article aims to develop a reindustrialization plan based on strategies to increase the relative participation of Brazilian industry in the Gross Domestic Product (GDP) in order to mitigate the Brazilian deindustrialization process. Method: the method used was DPSIR (Driving Forces, Pressures, State, Impacts, and Responses) in order to map information from specialists directly involved in the theme of industrial development in the areas of economics, public law, scientific research, public management, and private management. In addition, the TOPSIS method was used to prioritize the specialists' responses in order of urgency of implementation. Findings: the main result of this work revealed the strategies that should be prioritized to promote the country's industrialization. Novelty: this research served as a basis for the elaboration of the Brazilian Reindustrialization Plan, presented at the end of the article.